Recent advances in the preservation of postharvest fruits using edible films and coatings: A comprehensive review. (30th August 2023) - Chavan, Prafull; Lata, Kiran; Kaur, Tanbeer; Rezek Jambrak, Anet; Sharma, Somesh; Roy, Swarup; Sinhmar, Archana; Thory, Rahul; Pal Singh, Gurvendra; Aayush, Krishna; Rout, Abhisek
Highlights: Fruits and vegetable spoilage caused by microorganism can compromise the food security. Consumer demand for healthy and quality fruit prompted the requirement for edible coatings/films. Biobased packaging materials are an emerging field in the food sector. Edible coating protects fruits and vegetable against microbial spoilage. Abstract: In recent years, there has been considerable growth in the creation of edible films and coatings, which is predicted to have a major impact on fruit quality in the coming years. Consumers want fresh fruits that are pesticide-free, good quality, high nutritional value, and a long shelf life. The use of edible coatings and films on fruits is an environmentally dependable approach to a creative solution to this problem. The application, recent trends, and views of coatings and edible films, as well as their impact on fruit quality, are presented in this article, along with a knowledge of their key roles and benefits. According to numerous studies, natural polymers are highly suited for use as packaging material for fresh fruits and can often be a viable alternative to synthetic chemicals. Plasticisers, surfactants, cross-linkers, antimicrobial agents, functional additives, nanoparticles, and fruit and vegetable residues can be used to alter the properties of edible coatings.